Fictional Zoography in Água viva by Clarice Lispector - Alencar, Katya Queiroz (2022)
The objective of this work is to discuss in Água viva (1973), by Clarice Lispector the literary exercise as a thinker of a “sacranimality” or primitive potential, especially the animalic, founding in the text itself and inventoried in this fiction by starting from the familiar stranger in search of the “thing”, the “X”; categories that the narrator leaves in becoming to speculate the otherness of being. To do so, it takes as main references assumptions about the bestiary arising from transcontextualizations of the imaginary of the Jewish tradition, in addition to philosophical-literary subsidies and philosophical reflections on the inhuman and Clarice's thinking literature. The hypothesis of this study is that Lispector, like the Jew, in a secularized perspective, elaborates in Água viva a thinking and self-knowledge literature, especially via a fictional zoography, looking for the origin or a type of primitive divinity of the letter that says about the living and, at the same time, problematizes in this way the limits between the human and the non-human. Thus, the narrator of Água viva takes over the world, making, in addition to the report of the animals, the report of the “thing” in search of itself for the Other or the Other in its radical difference.